Ethnobotanical survey and biological properties of medicinal plants used for traditional maternal healthcare in Katsina State, Nigeria - Kankara, Sulaiman Sani (2015)
In Katsina State, Northern Nigeria, medicinal plants are widely used for the management of many medical conditions including maternal health since time immemorial. In this study, an ethnobotanical survey was conducted using semistructured questionnaire method to obtain information on the use of medicinal plants for traditional maternal healthcare in the study area. The respondents comprised of herbalists, traditional birth attendants (TBAs), traditional medical practitioners (TMPs), housewives, farmers and others. 111 medicinal plants belonging to 101 genera, distributed across 50 families were documented. Acacia nilotica (L) Delile and Guiera senegalensis J.F Gmel had the highest Relative Frequency of Citations (RFC) and Fidelity Levels (FL). 22.52% of the cited species belong to Fabaceae family followed by Asteraceae (7.21%), Malvaceae (5.41%) and Anacardiaceae (4.51%). 25.23% of the cited species are used for general wellbeing during and after pregnancy. 68.47% of the cited species were herbs and shrubs and 84.68% of them are sourced from the wild. Leaves were the most frequently used plant’s part (32.14%). 32% of the medications are prepared as decoctions and preparations are mostly (84.68%) administered orally. A literature survey was conducted with the aid of online database, text books and unpublished theses using keywords such as “biological activities”, “ethnobotanical uses”, “medicinal properties”, “toxicity studies” and the name of the species under review. Only species that have the combination of Relative Frequency of Citation (RFC) and Fidelity Level (FL) of at least 0.50 and 50%, respectively, were included for the literature survey. The literature survey revealed that with the exception of Acacia nilotica, Euphorbia convolvuloides and Indigofera astragalina DC, all the species reviewed had one or more reported biological activity substantiating its folkloric use in managing maternal health related conditions. The survey also disclosed that some of the surveyed plants are toxic. Species like Jatropha carcus and Ipomoea asarifolia were reported to be highly toxic to humans. Acanthospermum hispidum, Artemisia annua, Citrus aurantifolia and Mangifera indica were reported to have adverse effects on pregnancy in rats. Anchomanes difformis and Euphorbia balsamifera were also reported to be highly toxic in mice and rats, respectively. No developmental toxicity of Guiera senegalensis was reported despite its wide use during pregnancy in the study area. Another study was also conducted to assess the wound healing properties of Acacia nilotica using Sprague Dawley rats. The wound healing parameters assessed include wound contraction rate, level of proinflammatory cytokines (IL-1β and TNF-α) and histopathological analysis of the wound area. Wounds were assessed on 7th and 14th post wounding days. The extract showed a good, dose-dependent DPPH-radical scavenging activity comparable to trolox (standard antioxidant). Topical application of A. nilotica cream significantly (P< 0.05) enhances wound contraction rate compared to the control groups in both 7th and 14th days of evaluation. The extract also significantly suppressed the expression of both IL-1β and TNF-α in dose-dependent manner throughout the study period. The histological analysis revealed that the extract treatment enhanced tissues regeneration. Another study was also conducted to evaluate the effects of extraction methods on the antioxidant properties of Guiera senegalensis. Extraction of G. senegalensis alone was found to be more effective than combining it with either E. balsamifera, I. asarifolia or both. Air drying appeared to be the best drying method as it produced significantly higher phenolic contents and antioxidant activities. Optimum extraction temperature was found to be 40ºC, while 60 minutes appeared to be best extraction time. Although addition of natron up to 5 mg/mL was found to increase the TPC and TFC values, both antioxidant assays (DPPH, FRAP and TAC) were significantly affected adversely. Finally, developmental toxicity of G. senegalensis leaves water extract on zebrafish (Danio rerio) embryo was also studied. Survival rate, hatching rate and teratogenic effects were used to assess the toxicity. Both survival rate and hatching rate were found to be significantly lowered by the higher doses of the extract. LC50 of the extract was found to be 61.88 mg/mL. The extract also induced some structural malformations including bent tail, curved body, embryo sac edema, short body length and spinal cord curving on the hatched embryo. This study provides the first ethnobotanical study on medicinal plants used for traditional maternal healthcare in Northern Nigeria. The results of this study if properly harnessed, hold a great potential in combating maternal mortality cases in the study area thereby achieving one of the United Nation’s Millennium Developmental Goals (MDGs). Future studies directed towards conserving the reported species and standardizing traditional herbal medicine are recommended.